What is the impact of Smoking on female fertility ? A Systematic Review - Sharly Ayu Puspita; Dini Gustiarini (International Medical Journal Corp. Ltd, 2025)
Introduction: Smoking is a significant public health concern with well-documented adverse effects on reproductive health. The toxins in cigarette smoke disrupt hormonal balances and physiological processes essential for conception and pregnancy. This systematic review aims to comprehensively assess the impact of tobacco use on female fertility, covering both natural conception and outcomes of assisted reproductive technologies (ART). Methods: This study adhered to the PRISMA 2020 guidelines. A systematic search was conducted across PubMed, Semantic Scholar, Springer, and Google Scholar using keywords related to female fertility, smoking, and reproductive outcomes. After screening 2,346 records and assessing 949 reports for eligibility, 22 studies were included in the final analysis. Results: The evidence shows that smoking significantly impairs natural fertility by increasing the time to pregnancy and raising the risk of an infertility diagnosis (OR 1.85) and ectopic pregnancy (OR 2.02). In ART, smokers experience significantly lower live birth rates (OR 0.52), reduced clinical pregnancy rates (OR 0.59), fewer retrieved oocytes, and a substantially higher miscarriage rate (OR 2.48) compared to non-smokers. Mechanistically, smoking is consistently associated with reduced Anti-Müllerian Hormone (AMH) levels, indicating diminished ovarian reserve. A clear dose-response relationship was identified, with heavier smoking linked to more severe outcomes. Discussion: The findings confirm that tobacco use is a potent reproductive toxin that compromises nearly every stage of the reproductive process, from oocyte quality to embryo implantation and development. The damage is not easily bypassed, even with advanced medical interventions. While the harm is evident, data on the reversibility of these effects after smoking cessation remains inconclusive, highlighting a critical knowledge gap. Conclusion: The evidence is overwhelming: smoking has a profoundly negative and multifaceted impact on female fertility. It is a significant barrier to achieving a successful pregnancy, regardless of the conception method. Therefore, smoking cessation counseling must be a primary and non-negotiable component of preconception and fertility care to preserve reproductive potential and improve pregnancy outcomes.